Is tocilizumab effective in cytokine release syndrome in patients diagnosed with COVID-19?: a retrospective preliminary study - Çalışkan, Gülbahar; Topal, Serra; Sayan, Ayça; Soylu, Nuri Burkay (The European Research Journal, 2022)
Objectives: Although the prognosis is good in the vast majority of patients who are diagnosed with COVID-19, there are cases in which Acute Respiratory Distress Syndrome (ARDS) and multiple organ failure occur rapidly and result in death in a short time. It has been reported that severe clinical presentation is caused by cytokine release syndrome, and studies are currently conducted on treatments to reduce mortality in these patients. There are studies reporting the positive effects of anti-Human IL-6 Receptor Monoclonal Antibody, tocilizumab (TCZ), which specifically inhibits the functions of IL-6, in cases with cytokine storm. Data on TCZ use in intensive care are very limited. Methods: The medical records of 20 patients diagnosed with COVID-19 who were treated with standard treatment and TCZ in the ICU were retrospectively reviewed. Results: Twenty patients were included in the review. Nine (45%) received TCZ. The median length of stay in the ICU was 20 days in the TCZ group, and 14 days in the standard treatment group (p = 0.21). Mortality rate was 22.2% in TCZ group and 45.5% in the standard treatment group (p = 0.27). Conclusions: At day 28, mortality rate and clinical improvement was not statistically different in patients receiving standard treatment with TCZ and patients in standard treatment group. Additional data are needed to understand the eficacy and safety of TCZ.